CORRECTIVE FEEDBACK AS PERCEIVED BY AN EFL TEACHER AND STUDENTS IN SPEAKING CLASSROOM - Yustika Nur Fajriah (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
Given the prominence of corrective feedback, particularly in educational context, has been reported by related studies in SLA (White, 1987; Lyster& Ranta, 1997). However, many teachers failed to develop second language acquisition through corrective feedback since they didnâ€™t meet the effective ways in giving error correction (Hendrickson, 1976 as cited in Krashen, 1982). Given to these concerns, this study aims to investigate corrective feedback used as perceived by both EFL teacher as well as students in speaking classroom. To collect the data, this study employed open ended questionnaire, and structured interview. The findings reveal that the teacher and students perceived positively toward the importance of corrective feedback used in their speaking performance. Additionally, the explicit feedback given at the end of the studentsâ€™ speaking applied by the teacher is also considered as an effective way to correct errors as perceived by students.Â